Hérnia diafragmática traumática crônica e fístula gastropleurocutânea - Rangel,Marcelo Fernandes (2001)
Traumatic diaphragmatic hernia is defined as a laceration of the diaphragm with an abdominal viscera herniation into the thorax. It is usually asymptomatic, with the exception of the cases with obstruction, strangulation, necrosis or perforation of the herniaded viscera. It is classified as acute, latent or chronic, in accordance with the evolutive period. At the latent phase, symptoms are indefinite and the radiological signals, which are suggestive of thoracic affections, are frequent and can induce a diagnosis error, leading to inadequate treatment.This article presents a case of chronic traumatic diaphragmatic hernia which was complicated by a gastricpleuralcutaneous fistula, due to an inadequate thoracic drainage. Considering that this is a chronic affection with an unquestionable surgical indication, due to the complications risk, it is essential to have a detailed diagnostic investigation, which aims at both avoiding an intempestive or inadequate therapeutics behaviour and reducing the affection morbimortality. Recently, the videolaparoscopic approach has proved to be more precise when compared to the other diagnostic methods, by direct visualization of the diaphragmatic laceration, allowing its correction by an immediate suture.